Regional Economic Integration in ASEAN: How far will it go? - Kabir, Shahriar; Salim, Ruhul (Institute of Southeast Asian Studies, 2014)
The Association of South East Asian Nations (ASEAN) is among several regional blocs that have received praise from economists for making significant progress towards developing intra- and extra-regional economic relationships. However, opinions differ over the extent of ASEAN’s potential for integration. This paper reviews the performance of and prospects for the group’s intra- and extra-regional integration. It also reviews the performance of individual members in order to assess whether ASEAN integration could potentially lead to a monetary union in the future. We provide an overview of trade performance and a comparison of three macroeconomic variables: inflation; interest; and exchange rates. We observe that ASEAN members are in a favourable position to form a strong economic zone in the near future, but adopting a common monetary policy is less plausible.